2016
DOI: 10.1007/s00213-015-4194-5
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram reversed the traumatic stress-induced depressed and anxiety-like symptoms but not the deficits of fear memory

Abstract: PTSD-induced mood dysfunction is psychopathologically different from PTSD-induced fear disruption in terms of disequilibrium of monoamines within the fear circuit areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 67 publications
1
40
1
Order By: Relevance
“…Several previous studies have observed behavioral effects of SPS that persist for several weeks. Increased anxiodepressive behavior is seen shortly after SPS and persists for at least 2-3 weeks (Ji et al, 2014;Khan & Liberzon, 2004;Lin, Tung, & Liu, 2016;Miao et al, 2014;Patki et al, 2014;Peng et al, 2010;Takahashi, Morinobu, Iwamoto, & Yamawaki, 2006), consistent with the increase in anxietylike behavioral changes observed here 1-2 weeks after stress. We found that elevated plus maze behavior and NSF returned to normal within 5 weeks of SPS in normal (wild type) rats.…”
Section: Long-term Effects Of Acute Stresssupporting
confidence: 85%
“…Several previous studies have observed behavioral effects of SPS that persist for several weeks. Increased anxiodepressive behavior is seen shortly after SPS and persists for at least 2-3 weeks (Ji et al, 2014;Khan & Liberzon, 2004;Lin, Tung, & Liu, 2016;Miao et al, 2014;Patki et al, 2014;Peng et al, 2010;Takahashi, Morinobu, Iwamoto, & Yamawaki, 2006), consistent with the increase in anxietylike behavioral changes observed here 1-2 weeks after stress. We found that elevated plus maze behavior and NSF returned to normal within 5 weeks of SPS in normal (wild type) rats.…”
Section: Long-term Effects Of Acute Stresssupporting
confidence: 85%
“…Defective DA signaling has been implicated in PTSD, including deficits in the reward and reinforcement circuits, decreased reward anticipation and reduced hedonic responses, reduced DA metabolites in cerebral spinal fluid following traumatic reminders, altered expression of striatal DA transporter, and polymorphisms in genes encoding DAT and DA receptors in PTSD patients (40). A reduced basal spiking rate of VTA DA neurons (55) and altered DA level (56) were reported in PTSD models. We have provided clear evidence of impaired fear suppression and the absence of potentiated activation of VTA DA neurons after SL, while DA-dmPFC connections appear to be largely intact.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that PTSD animals treated with OLE had significant increases in 5-HT levels in the hippocampus and that this may have inhibited the pathophysiology of PTSD. The effects of OLE can be reversed by 5-HT manipulation (Lin et al 2016 ). Thus, the present findings indicate that OLE, like FLX, attenuates the behavior and neurochemical responses associated with anxiety by modulating NPY expression and the serotonergic system in the brain (Aykaç et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%